Description of cases of child sexual violence in indonesia from 2018 to 2022 (literature review) - A Rusman, Andri; Ismail, Mirza; Salman, Adam (ACTA Medical Health Sciences, 2024)
Sexual violence against children in Indonesia has been a pervasive issue that largely remains concealed, resembling the phenomenon of an iceberg. The Indonesian Child Protection Commission (KPAI) reported that there was a significant increase in the number of children who were victims of sexual violence in 2020. Children are particularly vulnerable to such violence, as they are often perceived as weak or powerless and are highly dependent on the adults in their environment. This study aims to describe cases of sexual violence against children in Indonesia from 2018 to 2022. The type of this research is a descriptive study, using a literature review approach by searching for various relevant sources through Google Scholar and Publish or Perish databases. The keywords used in the research for relevant articles include violence, sexual violence, child sexual violence, victims, perpetrators, risk factors. A total of 17 articles were selected for analyses using a synthesis matrix, obtaining following results: (1) The majority child victims of sexual violence were aged 12 to under 18 years old and were predominantly female; (2) Most perpetrators of sexual violence were over 18 years of age and predominantly male; (3) A significant number of perpetrators were part of extra-familial groups; (4) The most prevalent form of sexual violence was penetration, (5) Most the risk factors for sexual violence were associated with familial aspects. DOI : 10.35990/amhs.v3n2.p91-105 REFERENCES Komisi Perlindungan Anak Indonesia. (2021). REFERENCES1.2021. Darus, D. N., & Permana, R. (2022). Kekerasan seksual terhadap anak: Bentuk kekerasan seksual pada anak dan pelaku kekerasan seksual pada anak. [Jurnal tidak disebutkan], 400–407. Jannah, N., & Irfani, A. (2021). Peran Komisi Perlindungan dan Pengawasan Anak Daerah Provinsi Kalimantan Barat dalam penanganan kekerasan seksual pada anak tahun 2021. Ilmu Bimbing Konseling Islam, 01(2), 48–56. Ivo, N. (2015). Kekerasan seksual terhadap anak: Dampak dan penanganannya. Sosio Info, 01(200), 13–28. Adnyana, I. G. H. E. (2021). Karakteristik kasus pada Visum Et Repertum dengan dugaan kekerasan seksual di RSUP Sanglah Denpasar. Jurnal Kedokteran, IX(1), 1248–1256. Arsawati, N. N. J., & Antari, P. E. D. (2021). Antitesis pemenuhan hak anak korban kekerasan seksual dalam sanksi adat: Studi di Desa Tenganan, Karangasem. Jurnal Magister Hukum Udayana, 10(1), 104. Rini, R. (2020). Dampak psikologis jangka panjang kekerasan seksual anak. IKRA-ITH Humaniora, 4(3), 1–12. Wismayanti, Y. F., O’Leary, P., Tilbury, C., & Tjoe, Y. (2019). Child sexual abuse in Indonesia: A systematic review of literature, law and policy. Child Abuse & Neglect, 95, 104034. https://doi.org/10.1016/j.chiabu.2019.104034 Rumble, L., Febrianto, R. F., Larasati, M. N., Hamilton, C., Mathews, B., & Dunne, M. P. (2020). Childhood sexual violence in Indonesia: A systematic review. Trauma, Violence, & Abuse, 21(2), 284–299. https://doi.org/10.1177/1524838018767932 Agustina, P. W., & Kusumaning Ratri, A. (2018). Analisis tindak kekerasan seksual pada anak sekolah dasar. Jurnal Kajian Teori dan Praktik Kependidikan, 3(2), 151–155. Noviani, P. U., Arifah, R., Cecep, C., & Humaedi, S. (2018). Mengatasi dan mencegah tindak kekerasan seksual pada perempuan dengan pelatihan asertif. Prosiding Penelitian dan Pengabdian kepada Masyarakat, 5(1), 48. Latjengke, A. P., Tomuka, D., & Kristanto, E. G. (2020). Gambaran kasus kejahatan kekerasan seksual di RS Bhayangkara Tingkat III Manado periode Januari 2017–Desember 2019. e-CliniC, 8(2). Suwandi, J., Chusniatun, C., & Kuswardani, K. (2019). Karakteristik kekerasan seksual terhadap anak perempuan di Wonogiri dan Boyolali. Jurnal Pendidikan Ilmu Sosial, 29(1), 65–77. Kusuma, A. P. U., Nasution, A., & Saputra Nasution, A. (2021). Faktor-faktor yang mempengaruhi kejadian kekerasan seksual terhadap siswa di SMA Muhammadiyah Kota Bogor. Promotor, 4(3), 192–198. https://ejournal.uika-bogor.ac.id/index.php/PROMOTOR/article/view/5586 Sulastri. (2018). Kekerasan seksual terhadap anak Indonesia. Jurnal Psikologi Malahayat, 1(2), 61–71. Scarvanovi, B. W. (2020). "Anak Melecehkan Anak": Dinamika psikologis child neglect sebagai akar permasalahan indikasi korban kekerasan seksual anak. Wacana, 12(2), 188–202. Sarianti, B., Hangabei, S. M., & Hukum, F. (2021). Faktor yang melatarbelakangi terjadinya kekerasan seksual pada anak dalam lingkungan keluarga. Jurnal IDEA Fakultas Hukum Universitas Muhammadiyah Bengkulu, 21–33. Zuhdi, I. Y. A. (2021). Gambaran latar belakang keluarga korban kekerasan seksual di Kabupaten Siak Sri Indrapura. Psychology Contemporary, 1(2), 61–66. Zuri, & Zakso, A. (2019). Penanganan pelecehan seksual anak di bawah umur di Kota Pontianak. (April), 1–19. Ocviyanti, D., & Khusen, D. (2019). Penanganan holistik pada kasus pelecehan seksual pada anak. Jurnal Indonesian Medical Association, 68(4), 176–179. https://mki-ojs.idionline.org/jurnal/article/view/822 Herlianto, B., Adnyana, I. G. A. N. S., Windiani, I. G. A. T., Alit, I. B. P., & Soetjiningsih, S. (2019). Karakteristik kekerasan seksual pada anak di RSUP Sanglah Denpasar. Medicina (Bali), 50(1). https://www.medicinaudayana.org/index.php/medicina/article/view/467 Sumampouw, N., Otgaar, H., & de Ruiter, C. (2020). The relevance of certain case characteristics in the successful prosecution of child sexual abuse cases in Indonesia. Journal of Child Sexual Abuse, 29(8), 984–1003. https://doi.org/10.1080/10538712.2020.1801930 Urbayatun, S., Asmorojati, A. W., & Agusta, R. (2023). Sexual harassment in boys: An overview of child victims and child perpetrators in Indonesia. Jurnal Ilmiah Peuradeun, 11(1), 1. https://journal.scadindependent.org/index.php/jipeuradeun/article/view/787 Siburian, M., & Maendrofa, A. (2021). Peranan Lembaga Swadaya Masyarakat (LSM) terhadap penanganan kasus tindak pidana kekerasan seksual pada anak. Jurnal RECTUM Tinjauan Yuridis Penanganan Tindak Pidana, 3(1), 100. http://jurnal.darmaagung.ac.id/index.php/jurnalrectum/article/view/822 Rahmansyah, A. R., Nabillah, N., & Nurjanah, S. (2022). Tindakan hukum terhadap anak sebagai korban pelecehan seksual yang dilakukan Herry Wirawan. Jurnal Indonesian Social Sains, 3(6), 956–964. https://jiss.publikasiindonesia.id/index.php/jiss/article/view/621 Napitupulu, Y. R., & Julio, B. A. (2023). Pelecehan seksual anak di bawah umur pada anak Indonesia. Jurnal Multidisiplin Indonesia, 2(10), 3088–3095. https://jmi.rivierapublishing.id/index.php/rp/article/view/582 Septiawan, D. A., Arviandi, R., & Lubis, A. (2024). Forensic medical findings in child sexual violence: A case report. Frontiers in Healthcare Research, 1(2), 30–34. https://frontiersin-healthcare-research.org/index.php/id/article/view/1528 Gámez‐Guadix, M., Almendros, C., Calvete, E., & De Santisteban, P. (2018). Persuasion strategies and sexual solicitations and interactions in online sexual grooming of adolescents: Modeling direct and indirect pathways. Journal of Adolescence, 63(1), 11–18. https://doi.org/10.1016/j.adolescence.2017.12.002 Zimmerman, G. M., Farrell, C., & Posick, C. (2017). Does the strength of the victim-offender overlap depend on the relationship between the victim and perpetrator? Journal of Criminal Justice, 48, 21–29. https://doi.org/10.1016/j.jcrimjus.2016.10.003 Ismiulya, F., Diana, R. R., Na’imah, N., Nurhayati, S., Sari, N., & Nurma, N. (2022). Analisis pengenalan edukasi seks pada anak usia dini. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 6(5), 4276–4286. https://obsesi.or.id/index.php/obsesi/article/view/2582 Knack N, Winder B, Murphy L, Fedoroff JP. Primary and secondary prevention of child sexual abuse. Int Rev Psychiatry [Internet]. 2019 Feb 17;31(2):181–94. Available from: https://www.tandfonline.com/doi/full/10.1080/09540261.2018.1541872 Dani MIW. Perlindungan Hukum Terhadap Anak Korban Kekerasan Seksual (Studi Peran Lembaga Swadaya Masyarakat Sahabat Anak, Perempuan, dan Keluarga di Kabupaten Bantul) [Skripsi]. Yogyakarta: Universitas Islam Indonesia; 2018. Halvorsen JE, Tvedt Solberg E, Hjelen Stige S. “To say it out loud is to kill your own childhood.” – An exploration of the first-person perspective of barriers to disclosing child sexual abuse. Child Youth Serv Rev [Internet]. 2020 Jun;113:104999. Available from: https://linkinghub.elsevier.com/retrieve/pii/S0190740919312745 Annisa SF. Children as Victims of Sexual Abuse: Has the Law Provided Enough Justice? Indones J Int Clin Leg Educ. 2020;2(4):435–48. Donne MD, DeLuca J, Pleskach P, Bromson C, Mosley MP, Perez ET, et al. Barriers to and facilitators of help-seeking behavior among men who experience sexual violence. Am J Mens Health [Internet]. 2018 Mar 22;12(2):189–201. Available from: https://journals.sagepub.com/doi/10.1177/1557988317740665 Rusman AA, et al. [Data tidak lengkap – mohon lengkapi data referensi ini jika ingin disertakan.] Jimmerson K. Police department management of sexual assault cases: A retrospective analysis [Thesis]. University of Colorado at Denver; 2016. Marques NM, Belizario GO, Rocca CC de A, Saffi F, de Barros DM, Serafim A de P. Psychological evaluation of children victims of sexual abuse: Development of a protocol. Heliyon [Internet]. 2020 Mar 1;6(3):e03552. Available from: https://doi.org/10.1016/j.heliyon.2020.e03552 Wulandari YA, Saefudin Y. Dampak psikologis dan sosial pada korban kekerasan seksual: Perspektif viktimologi. J Rev Pendidik dan Pengajaran. 2024;7(1):296–302. Hatta K. Peran orangtua dalam proses pemulihan trauma anak. Gend Equal Int J Child Gend Stud. 2015;1(2):57–74. Dubrow N, Liwski NI, Palacios C, Gardinier M. Helping child victims of violence. In: International Responses to Traumatic Stress [Internet]. Routledge; 2018. p. 327–46. Available from: https://www.taylorfrancis.com/books/9781351843522/chapters/10.4324/9781315224312-13 Hagemann-White C, Humphreys C, Tutty LM, Diemer K. Overview of current policies on arrest, prosecution, and protection by the police and the justice system as responses to domestic violence. In: Critical Issues on Violence Against Women. Routledge; 2014. p. 47–65.